Moringa oleifera: A Bibliometric Analysis of International Publications during 1935-2019 - Gupta, BM; Ahmed, K.K. (Pharmacognosy Reviews)
The paper examines quantitative and qualitative aspects of research on Moringa oleifera, based on global publications output (3187 publications), as covered in Scopus database during 1935-2019. The publications on Moringa oleifera registered annual average growth of 16.18% and cumulative growth of 3594.0% and averaged to 17.69 citations per paper. Bulk of global publications output (76.72%) and the global citations (68.06%) in the field emanates from top 10 countries. The paper further provides an insight into qualitative performance of research on Moringa oleifera in terms of relative citation index, citations per paper, highly cited papers, besides analyzing the top 25 global organizations and authors in the field, the distribution of publications by broad subjects, the identification of the most significance keywords, the most productive journals and the analysis of higher-cited papers in the field. The study found that Universidade Estadual de Maringa, Brazil (72 papers), National Research Centre, Giza, Egypt (66 papers) and University of Agriculture, Faisalabad, Pakistan (65 papers) were the most productive organizations and University of Agriculture, Faisalaba, Pakistan (38.35 and 2.17), University of Karachi, Pakistan (35.23 and 1.99) and Mahidol University, Thailand (27.35 and 1.55) were the most significant organizations in terms of citation per paper and relative citation index. Similarly, R. Bergamasco. (65 papers), P.M.G. Paiva. (36 papers) and L.C.B.B Coelho (34 papers) were the most productive authors and F. Anwar. (124.21 and 7.02), J. Beltrán-Heredia (36.07 and 2.04) and J. Sánchez-Martín (34.69 and 1.96) were the leading authors in terms of citation per paper and relative citation index. South African Journal of Botany (62 papers), Journal of Ethnopharmacology (61 papers) and Desalination and Water Treatment (44 papers) were the leading journals contributing to the field.
Keywords: Moringa oleifera; Medicinal plant; Global publications; Scientometrics; Bibliometrics